CONDITION OF DECENTRALIZATION AND ORGANIZATIONAL LEGAL FORMS OF SUSTAINABLE DEVELOPMENT OF REGIONS OF UKRAINE IN THE CONTEXT OF THE GLOBAL EXPERIENCE - Kulchytska , N.Ye. (The actual problems of regional economy development, 2016)
In the article the modern condition of decentralization and organizational legal forms of sustainable development of regions of Ukraine in the context of the global experience are analyzed, possible ways to overcome regional disparities are proved. A special place in scientific research article takes a significant number of modern researchers analyzed the theoretical and methodological foundations of a system of financial support of local authorities in the transition to decentralization of public administration. In this regard, particular relevance is the problem of defining the role of decentralization principles in forming the financial support of local government. The importance of decentralization in the process of local government reform is proved. The ways implementing decentralization in modern Ukraine are shown. The scientific approaches to determining the meaning and role of decentralization in a market economy are analyzed and summarized. JEL: H 32